Pemanfaatan Perangkat Lunak Arcinfo?rccview Untuk Pemutakhiran Basis Data Spasial Dalam Sistem Informasi Geografi Pajak Bumi Dan Bangunan - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Pasca Sarjana UGM, 2004)
ABSTRAK Following the rapid changes during the regional autonomy in Indonesia, land data have also changed rapidly. This requires proper maintenance of land database in order to keep the data up to date. Insufficient facilities required for database maintenance of SIG-PBB (Geographic Information System of Land and Building Tax purposes) have caused inconsistency between spatial data maintained in SIG-PBB and the associated attribute data (non-spatial data) maintained in SISMIOP (Property Tax Information and Management System) database. This research aimed at developing procedures for PBB spatial data updating. This research used ArcInfo version 3.5 and Are View version 3.2 package software. The research utilized modules available in both Archzfo and Arc View to update the spatial database of SIG-PBB in relation with the regional changes. Stages in the research include format data conversion from Mapinfo to Archzfo/ArcView, PBB spatial data editing, PBB attribute data editing, and format data conversion from Arclnfo/ArcView back to Mapinfo. The research yields up to date PBB spatial data, that are ready to use as input in SIG-PBB applications. In addition, the research evaluates the speed of data input and updating processes using Archifb/ArcView package software in different computer specifications. Keywords: spatial database, SIG-PBB, ArcInfo/AreView